Galaxy And Mass Assembly (GAMA): the 325 MHz radio luminosity function of AGN and star-forming galaxies. Issue 1 (23rd January 2016) - Prescott, Matthew; Mauch, T.; Jarvis, M. J.; McAlpine, K.; Smith, D. J. B.; Fine, S.; Johnston, R.; Hardcastle, M. J.; Baldry, I. K.; Brough, S.; Brown, M. J. I.; Bremer, M. N.; et al.
Abstract: Measurement of the evolution of both active galactic nuclei (AGN) and star-formation in galaxies underpins our understanding of galaxy evolution over cosmic time. Radio continuum observations can provide key information on these two processes, in particular via the mechanical feedback produced by radio jets in AGN, and via an unbiased dust-independent measurement of star formation rates. In this paper, we determine radio luminosity functions at 325 MHz for a sample of AGN and star-forming galaxies by matching a 138 deg 2 radio survey conducted with the Giant Metrewave Radio Telescope, with optical imaging and redshifts from the Galaxy And Mass Assembly survey. We find that the radio luminosity function at 325 MHz for star-forming galaxies closely follows that measured at 1.4 GHz. By fitting the AGN radio luminosity function out to z = 0.5 as a double power law, and parametrizing the evolution as Φ ∝ (1 + z ) k, we find evolution parameters of k = 0.92 ± 0.95 assuming pure density evolution and k = 2.13 ± 1.96 assuming pure luminosity evolution. We find that the Low Excitation Radio Galaxies are the dominant population in space density at lower luminosities. Comparing our 325 MHz observations with radio continuum imaging at 1.4 GHz, we determine separate radio luminosity functions for steep- and flat-spectrum AGN, and show that the beamed population of flat-spectrum sources in our sample can be shifted in number density and luminosity to coincide with the unbeamed population of steep-spectrum sources, as is expected in the orientation-based unification of AGN.